Digital Media Integration In English Language Teaching: Its Impact On Young Learners' Speaking Confidence And Engagement - Rini Artika; Wahyuni Fitria; Eliza Trimadona (Lembaga Riset dan Inovasi Almatani, 2026)
This study examines the integration of digital media in English language teaching and its impact on young learners’ speaking confidence and classroom engagement at the primary school level. Conducted at Excellent Mandiri School, Kota Jambi, Indonesia, this qualitative study employed structured classroom observations across twelve English lessons involving fourth- to sixth-grade elementary students. A systematic observation protocol was used to identify indicators of speaking confidence, including voluntary oral participation, spontaneous English production, and avoidance behaviors, as well as student engagement across various learning activities. The findings demonstrate a clear difference between digital media-supported and non-digital learning phases. Digital media activities generated substantially higher levels of speaking confidence, with positive speaking behaviors occurring more than twice as often as those observed during conventional instruction. Students also showed high engagement rates across digital activities, ranging from 74% to 95%, compared with 48% during teacher-centered explanations. Animated educational videos and digital songs encouraged sustained participation, while interactive quiz applications stimulated the highest level of active involvement. Differences among learner responses and the gradual increase in confidence indicators suggest that digital media integration serves not only as a motivational tool but also as a mechanism for developing communicative confidence over time. These findings highlight the importance of purposeful digital media integration in primary EFL classrooms and provide implications for teacher development, curriculum innovation, and educational policy in Indonesia.